Modelling the inner debris disc of HR 8799 - Contro, B.; Horner, J.; Wittenmyer, R. A.; Marshall, J. P.; Hinse, T. C. (Monthly notices of the Royal Astronomical Society, 2016)
In many ways, the HR 8799 planetary system strongly resembles our own. It features four giant planets and two debris belts, analogues to the Asteroid and Edgeworth-Kuiper belts. Here, we present the results of dynamical simulations of HR8799's inner debris belt, to study its structure and collisional environment. Our results suggest that HR 8799's inner belt is highly structured, with gaps between regions of dynamical stability. The belt is likely constrained between sharp inner and outer edges, located at ∼6 and ∼8 au, respectively. Its inner edge coincides with a broad gap cleared by the 4:1 mean-motion resonance with HR 8799e. Within the belt, planetesimals are undergoing a process of collisional attrition like that observed in the Asteroid belt. However, whilst the mean collision velocity in the Asteroid belt exceeds 5 km s−1, the majority of collisions within HR 8799's inner belt occur with velocities of order 1.2 km s−1, or less. Despite this, they remain sufficiently energetic to be destructive – giving a source for the warm dust detected in the system. Interior to the inner belt, test particles remain dynamically unstirred, aside from narrow bands excited by distant high-order resonances with HR 8799e. This lack of stirring is consistent with earlier thermal modelling of HR 8799's infrared excess, which predicted little dust inside 6 au. The inner system is sufficiently stable and unstirred that the formation of telluric planets is feasible, although such planets would doubtless be subject to a punitive impact regime, given the intense collisional grinding required in the inner belt to generate the observed infrared excess.